Association of TSPO-PET-measurable hippocampal inflammation with cognitive symptoms in multiple sclerosis - Du Bose, Brittany (My University, 2021)
One of the major symptoms of multiple sclerosis is cognitive decline, which includes worsening memory (verbal, visuospatial, etc.), attention, processing speed, and executive functions. The volume and mass of the hippocampus is known to correlate with cognition, and its atrophy marks the beginning stages of cognitive decline for patients suffering from multiple sclerosis. In this study, the radioligand 11C-PK11195 was used with PET to image TSPO binding in the hippocampus of patients with multiple sclerosis and in healthy controls to compare DVR values between the two groups. Volume differences were measured with MRI among controls, patients, and the subgroups of patients that have been divided into cognitively functional (CF) and cognitively impaired (CI) groups. Significant differences between DVR and hippocampal volume were not found between either of the groups. Significant associations were not found between DVR, volume, and cognitive functioning as measured by neuropsychological testing.
Keywords: Multiple sclerosis, cognitive decline, hippocampus, TSPO, neuroinflammation, PET, MRI